Cincinasura, a new genus for Miltochrista synestramena Hampson (Lepidoptera: Erebidae: Arctiinae) with a new species from Indonesia - Volynkin, Anton V.; Černý, Karel (Zootaxa, 2021)
The new genus Cincinasura gen. n. is described for the type species Asura synestramena Hampson, 1900. A new species, Cincinasura cyclophora sp. n. is described from the island of Sulawesi (Indonesia). A new combination is established: Cincinasura synestramena (Hampson, 1900), comb. n. Adults together with male and female genitalia of the new and similar genera are illustrated.